The Dark Side of Neutron Stars - Chris Kouvaris (Advances in High Energy Physics)
We review severe constraints on asymmetric bosonic dark matter based on observations of old neutron stars. Under certain conditions, dark matter particles in the form of asymmetric bosonic WIMPs can be effectively trapped onto nearby neutron stars, where they can rapidly thermalize and concentrate in the core of the star. If some conditions are met, the WIMP population can collapse gravitationally and form a black hole that can eventually destroy the star. Based on the existence of old nearby neutron stars, we can exclude certain classes of dark matter candidates.